Phagocytosis of yeasts by lipopolysaccharide (LPS)-stimulated macrophages: Yeast ingestion by LPS-stimulated macrophages - Mahmoudi, Mohammad; Taghavi-Farahabadi, Mahsa; Hashemi, Seyed Mahmoud; Mousavizadeh, Kazem; Rezaei, Nima; Mojtabavi, Nazanin (Student Research in Translational Medicine, 2023)
For phagocytosis measurement, 5×105 macrophages were seeded in a 12-well plate. 20 ng/ml LPS was added to cells to induce the M1 phenotype. After 24h the medium was changed. A suspension of heat-killed baker’s yeast was prepared at 108 particles per ml in DMEM medium. The yeast suspension was added to macrophages at a ratio of 1:10 (macrophage: yeast). Macrophages were allowed for 60 minutes to phagocyte the particles at 37°C. To remove the free yeasts, the well was washed with PBS. The phagocytosis was observed using an inverted microscope.